Effect of Longan Leaf Extract on Blood Glucose Tolerance and Langerhans Islets of Mice with type 2 Diabetes Mellitus - Parawestri, Putri Devika; Kuswanti, Nur (LenteraBio : Berkala Ilmiah Biologi, 2025)
Blood glucose tolerance is an important measure of how the body regulates glucose levels. It is caused by insulin resistance, pancreatic β-cell dysfunction, excess glucose production by the liver, defective glucose utilization in peripheral tissues, or oxidative stress. This study was aimed to analyse the effect of longan leaf extract on blood glucose tolerance and pancreas alteration in rats with type 2 diabetes. In this study, a completely randomized design was utilized with six groups: a negative control, a positive control (HFD + alloxan monohydrate), a group that received metformin, and three additional groups receiving longan leaf extract at doses of 28, 42, and 56 mg/kg body weight. Treatments were administered for seven days. Blood glucose tolerance was assessed on day eight, while pancreatic histopathology was evaluated through measurement of Langerhans islet diameter in pancreatic sections. Blood glucose tolerance data were analysed with the Kruskal–Wallis test followed by the Dunnett test, whereas pancreatic histopathology data were analysed using ANOVA and Duncan’s test. The results showed that longan leaf extract significantly affected blood glucose tolerance and pancreatic histopathology in type 2 diabetic mice. The dose of 56 mg/kg body weight demonstrated the most effective improvement, enhancing glucose tolerance and increasing the diameter of Langerhans islets.